2022
DOI: 10.3390/ani12172278
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Phytogenic Extracts Favorably Influence Productivity, Egg Quality, Blood Constituents, Antioxidant and Immunological Parameters of Laying Hens: A Meta-Analysis

Abstract: The present study aimed to assess the impact of dietary phytogenic extracts on laying hen productivity, egg quality, blood constituents, antioxidant, and immunological parameters through a meta-analytical approach. A total of 28 articles (119 data points) reporting the influence of dietary phytogenic extracts on the productive performance, egg quality, blood constituents, immunological, and antioxidant parameters of laying hens were embedded into a database. Statistical analysis was performed using a mixed mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 66 publications
(53 reference statements)
3
10
0
Order By: Relevance
“…This was probably due to the fact that the tannins were fed with nutraceuticals and had a predominantly inhibitory effect on the digestive process, and, consequently, the poultry of this group grew more slowly. In the later growing periods from 8–14 days, it did not affect the growth rate of the poultry in this study (200–500 g/t), which was also observed in several other studies [ 45 , 46 , 47 , 48 ], even with very wide dose ranges (200–800 g/t) [ 34 , 36 , 49 , 50 ]. In addition, when analyzing poultry productivity in early studies, Zaikina et al (2022) [ 9 ], conducted on Cobb 500 cross broilers, found that the optimal dosage of phytobiotics for up to 10 days of tannin-based rearing was 800 g/t, while the dosage of 500 g/t ( p < 0.05) proved to be worse than an antibiotic.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This was probably due to the fact that the tannins were fed with nutraceuticals and had a predominantly inhibitory effect on the digestive process, and, consequently, the poultry of this group grew more slowly. In the later growing periods from 8–14 days, it did not affect the growth rate of the poultry in this study (200–500 g/t), which was also observed in several other studies [ 45 , 46 , 47 , 48 ], even with very wide dose ranges (200–800 g/t) [ 34 , 36 , 49 , 50 ]. In addition, when analyzing poultry productivity in early studies, Zaikina et al (2022) [ 9 ], conducted on Cobb 500 cross broilers, found that the optimal dosage of phytobiotics for up to 10 days of tannin-based rearing was 800 g/t, while the dosage of 500 g/t ( p < 0.05) proved to be worse than an antibiotic.…”
Section: Discussionsupporting
confidence: 89%
“…Modern industrial poultry farming, both urgent and broiler, is widely used all over the world by many approaches or alternative natural feed additives in feed to increase productivity, improve animal welfare and, ultimately, achieve the sustainability of animal husbandry [ 2 , 3 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 33 ]. Of course, the ban on the use of antibiotics when feeding poultry and other types of productive farm animals has positively affected the increase in alternative sources of biologically active substances, such as pro- and prebiotics [ 10 , 11 , 22 , 27 ], enzymes [ 11 , 34 ], symbiotics [ 27 , 34 ], organic acids [ 35 , 36 , 37 , 38 , 39 ], essential oils [ 10 , 11 , 13 , 20 ], medicinal herbs [ 36 , 40 , 41 ], phytobiotics [ 7 , 8 , 9 , 11 , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous dietary antioxidants are widely accepted as effective substances for mitigating the adverse effects of HS on breeder hens in terms of favorable productive and reproductive performance, immunity, embryonic development, and antioxidant activity ( Ibtisham et al, 2019 ; Amevor et al, 2021 ; Darmawan et al, 2022 ). Our results revealed the beneficial effects of synthetic (vitamins C, E, Se, and L-carnitine) and phytogenic (clove, green tea pomace, and Vietnamese coriander) antioxidants on egg production, hatchability, embryo development, and antioxidant activity of breeder hens under HS.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that after LPS stimulation induces an immune stress response, the body's immune response is activated, causing plasma cells to rapidly secrete large amounts of IgM and IgG, and mucosal epithelial cells to secrete SIgA for defense against undesirable attacks ( Ramadan et al, 2020 ). Polyphenolic compounds from medicinal plants have been reported to have immunoprotective properties and immunomodulatory potential in poultry organisms ( Darmawan et al, 2022 ). As an active polyphenol, RES can benefit the immune response by binding IgG through an additional ligand to the Fc receptor ( Nimmerjahn and Ravetch, 2010 ).…”
Section: Discussionmentioning
confidence: 99%